PHOTOCATALYTIC DEGRADATION OF METHYLENE BLUE IN AQUEOUS SOLUTIONS BYTIO2-SIO2 CATALYST (FUDMA JOURNAL OF SCIENCES, 2023)
The research was aimed at studying the Photocatalytic decompositions of methylene blue (MB) in aqueous solutions using titanium-based catalyst.. The catalyst was prepared by supporting titanium (IV) oxide on Silica (SiO2). The physicochemical characteristic of the catalyst was obtained using Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD) and Fourier Transform infrared spectroscopy (FTIR). The diffraction patterns showed strong peaks that are assigned to titania anatase phase and weaker peak(s) that indicated low rutile phase. The FTIR spectra showed broad peaks of Ti-O-Ti linkages in TiO2 particles. The catalyst was tested in visible light or UV irradiation at 254 nm or 365nm and was found to be active in the decomposition of Methylene blue from aqueous solutions. The kinetic of decomposition of MB was evaluated and found to be better represented by lagergren pseudo-second order model. The applicability of this model was expressed by the linearized plot of (t/qt) versus t.
Keywords: Photocatalytic, Methylene Blue, Dye, Degradation, Catalyst